Self-Enforcing Intergenerational Social Contract as a Source of Pareto Improvement and Pollution Mitigation - Thang Dao; Kerstin Burghaus; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We contribute to the literature on private financing of intergenerational public goods, focusing on climate change mitigation. We consider, in a general equilibrium overlapping generations (OLG) model with environmental externalities, a contract between successive generations, whereby agents of the current working-age generation invest a share of their labor income in pollution mitigation in exchange for a transfer to their old-age capital income paid by the next generation. We show that the existence of a contract which is Pareto-improving compared to an equilibrium without contract requires a minimum level of income and we characterize the set of Pareto-improving mitigation-transfer combinations. Nash bargaining yields unique solutions for the mitigation share and transfer rate respectively which increase in income. We prove that Nash bargaining leads to a steady state with lower pollution stock and higher income compared to the steady state without a contract and we study transitional dynamics. Notably, simulation shows that delaying the implementation of a social contract for too long may have considerable welfare costs: Income inevitably falls below the threshold in finite time so that Pareto improving mitigation is no longer possible and the economy converges to a steady state with high pollution stock and low income. In the second part of the paper, we study a game theoretic setup with overlapping generations, taking into account that credibly committing to a contract might not be possible. We show that if transfers are granted as a subsidy to capital income, there exist mitigation transfer schemes which are both Pareto improving and give no generation an incentive to deviate from the contract even in the absence of population growth. Further, the complete crowding out of investment incurred with lump sum transfers is avoided in our setup.
Keywords: D62; D64; E21; Q54; 330; OLG models; mitigation; Pareto improvement; social contract